Disruption in the apparel industry? Automation, employment and reshoring. (28th October 2021) - BÁRCIA DE MATTOS, Fernanda; EISENBRAUN, Jeff; KUCERA, David; ROSSI, Arianna
Abstract: Amid concern about the impact of automation on employment, there is consensus that jobs comprising repetitive codifiable tasks are at greatest risk. The apparel industry has been strategic in economic development as an entry point into global markets and as a creator of jobs. Although routine work characterizes the bulk of employment in apparel manufacturing, the penetration of automation technologies remains limited. Drawing on interviews with key personnel at leading apparel brands, this article offers new insights into the current and projected use of technology, identifying practical bottlenecks and discussing potential implications for the global distribution of production and employment.